Optimalisasi Pemda Palas Dalam Menanggulangi Tingkat Volume Sampah Di Kec. Barumun - Hasibuan, Pardamean; Siregar, Mardona (Jurnal El-Thawalib, 2022)
This research examines the role of DLHK in the implementation of article 21 of Padang Lawas District Regulation No. 2 of 2014 concerning Garbage from the perspective of Fiqh Siyasah. This research is a field research and was compiled using an empirical normative approach, the primary data source comes from Padang Lawas District Regulation No. 2 of 2014 concerning Trash Cans and secondary data comes from books and journals related to this research. While the data collection techniques used in this study consisted of interviews, observation and documentation and data analysis techniques using qualitative descriptive techniques. The results of this study state that the role of DLHK Padang Lawas Regency in implementing article 21 of Regional Regulation of Padang Lawas Regency Number 02 of 2014 concerning Trash Cans has not been implemented effectively. Because the socialization that has been carried out has not been evenly distributed and the distribution of trash cans that are not on target. Then from a review of siyasa dusturiyah studies. The role of DLHK in implementing Article 21 of Regional Regulation Number 2 of 2014 has not been implemented properly.